Accounting and the Law–Cases and Materials (Book). - Cannon, Arthur M.; Moonitz, Maurice (The Accounting Review, 1953)
Reviews the book "Accounting and the Law–Cases and Materials," by James L. Dohr, George C. Thompson and William C. Warren.